42.8k views
25 votes
Given that f(x) = 3x + 1 and g(x)=x2 - 2x-6, find (gof)(5).

User Edumelzer
by
5.3k points

1 Answer

7 votes

Answer:

(gof)(5)=1246

Explanation:

first lets find for (gof)

(gof)=g(f(x))

=x(3x+1)^2-2(3x+1)-6

=x(9x^2+6x+1)-6x+2-6

=9x^3+6x^2+x-6x-4

=9x^3+6x^2-5x-4

now let's find for (gof)(5)

we know(gof)=9x3+6x2-5x-4

so (gof)(5)=9(5)^3+6(5)^2-5(5)-4

=9(125)+6(25)-25-4

=1125+150-29

(gof)(5)=1246

User Richelle
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.